What Is a Trauma Informed Classroom? What Are the Benefits and Challenges Involved? - Sweetman, Norah (Frontiers in Education, 2022)
This paper investigates the elements of a ‘trauma informed classroom’. The origins of this approach lie in the developing understanding of Adverse Childhood Experiences (ACES) and their significant life-long negative effects on development in all areas of life. Children and young people affected by traumas such as living with addiction, domestic violence or severe neglect are currently attending educational institutions. There are also young refugees, who are victims of state sponsored violence and brutality. These young people frequently struggle with concentration and may also have relational and behavioural difficulties. Logistical difficulties around attendance, resources, and PTSD type symptoms add to their burden and lead to dropping out or gaining a reputation as a troublemaker or incapable student. The foundation of the ‘trauma informed classroom’ is an understanding by teachers of the daily circumstances of their pupils’ lives, and awareness of what trauma-based reactions and behaviours look like. The rituals and teaching methods of the classroom may be modified in response to the pupils’ needs, in consultation with them, and in a system of ongoing feedback. This work necessitates a collaborative team to support the teacher, and access relevant services. The benefits and challenges for pupils and teachers will be explored.